Global trends and hotspots in research of robotic surgery in oncology: A bibliometric and visual analysis from 2002 to 2021 - Lu, Hua; Han, Tingliang; Li, Fangcun; Yang, Jiali; Hou, Zhaomeng (Frontiers in Oncology, 2022)
Background: With the development of robotic surgery in the field of oncology, an increasing number of relevant research papers have been published. In order to explore the research hotspots and trends in this field, a bibliometric and visual analysis was performed for the first time. Methods: The literature records related to oncology robotic surgery were obtained from the Web of Science Core Collection database and imported into the software VOSviewer 1.6.18, CiteSpace 6.1.R3, and the Bibliometric Online Analysis Platform for analysis. Results: A total of 6,964 publications, including 5,635 articles and 1,329 reviews, were included in this study. Over the past 20 years, annual publications and citations have experienced rapid growth, particularly in the last two years. The United States was the country with the most publications, while Yonsei University in South Korea was the most productive institution. The Journal of Robotic Surgery and the Journal of Urology were the journals with the most publications and citations, respectively. Mottrie A from Belgium and Ficarra V from Italy were the authors with the highest number of publications and citations, respectively. The keywords “robotic surgical procedure”, “laparoscopic surgery”, “prostate cancer”, “colorectal cancer”, “gastric cancer”, “resection”, “complications classification”, “open surgery”, “transoral robotic surgery”, “pathological outcomes”, and “robot-assisted surgery” reflect the research hotspots and trends of oncology robotic surgery. Conclusion: The therapeutic advantages of robotic surgery in oncology are not yet prominent, and further randomized controlled trials with multicenter and large samples are needed to evaluate the advantages of robotic surgery compared with laparoscopic surgery and open surgery in the treatment of tumors from multiple outcome indicators.